The Use of ACE inhibitor/ARB in SARS-CoV-2 Patients: A Comprehensive Narrative Review - Hariyanto, Timotius Ivan; Japar, Karunia Valeriani; Damay, Vika; Kwenandar, Felix; Sieto, Novia Lauren; Kurniawan, Andree (Asian Journal of Medical Sciences, 2020)
The three most common comorbidities that are associated with increased mortality in COVID-19 patients are Hypertension, Diabetes, and Cardiovascular disease, Angiotensin-converting enzyme (ACE) inhibitors and Angiotensin II receptor blockers (ARB) are the drugs most commonly prescribed for the management of these diseases. Recent experimental study in animals and humans have found that SARS-CoV-2 uses ACE2 as the receptors for entry. Moreover, in an animal study, the use of ACE inhibitor/ARB increases the level of ACE2 expression that can lead to increased SARS-CoV-2 infectivity. On the other side, some evidences suggest that the ACE2 receptor is not necessary for SARS-CoV-2 entry into the cell and suggested that there is a cofactor that play part. Experimental studies in humans also showed that there is no association between ACE inhibitor/ARB with SARS-CoV-2 infectivity and mortality. In conclusion, there is still insufficient data to stop the use of inhibitor/ARB in SARS-CoV-2 patients. Therefore, we suggested that in line with the recommendations from ESC and AHA/ACC, the use of these two drugs in SARS-CoV-2 patients with cardiovascular comorbidity should still be continued.